Construction and validation of a predictive risk model for nosocomial infections with MDRO in NICUs: a multicenter observational study - Zhou, Jinyan; Luo, Feixiang; Liang, Jianfeng; Cheng, Xiaoying; Chen, Xiaofei; Li, Linyu; Chen, Shuohui (Frontiers in Medicine, 2023)
This study aimed to construct and validate a predictive risk model (PRM) for nosocomial infections with multi-drug resistant organism (MDRO) in neonatal intensive care units (NICUs), in order to provide a scientific and reliable prediction tool, and to provide reference for clinical prevention and control of MDRO infections in NICUs.This multicenter observational study was conducted at NICUs of two tertiary children's hospitals in Hangzhou, Zhejiang Province. Using cluster sampling, eligible neonates admitted to NICUs of research hospitals from January 2018 to December 2020 (modeling group) or from July 2021 to June 2022 (validation group) were included in this study. Univariate analysis and binary logistic regression analysis were used to construct the PRM. H-L tests, calibration curves, ROC curves and decision curve analysis were used to validate the PRM. Results: 435 and 114 neonates were enrolled in the modeling group and validation group, including 89 and 17 neonates infected with MDRO, respectively. 4 independent risk factors were obtained and the PRM was constructed, namely: P=1/ (1+ e −X ), X=-4.126+1.089× (low birth weight) +1.435× (maternal age ≥35 years) +1.498× (use of antibiotics >7 days ) +0.790× (MDRO colonization). A nomogram was drawn to visualize the PRM. Through internal and external validation, the PRM had good 3 / 24 fitting degree, calibration, discrimination and certain clinical validity. The prediction accuracy of the PRM was 77.19%.Prevention and control strategies for each independent risk factor can be developed in NICUs. Moreover, clinical staff can use the PRM to early identification of neonates at high risk, and do targeted prevention to reduce MDRO infections in NICUs.